Considerations for patients with psoriasis travelling under immunosuppression. (25th January 2021) - Stephan, Brigitte; Tittelbach, Jörg; Bühler, Silja
Summary: With the establishment of modern systemic therapies for psoriasis, comprehensive consultation is required for travelling with immune modulation. Logistic aspects regarding transport and storage, climatic peculiarities of the country of travel and drug dependent risks regarding infections must be considered. Vaccinations and preventive measures are emphasized. Depending on the current national recommendations, special features of vaccinations while under immunosuppression must be taken into account.